2022
DOI: 10.5194/hess-26-5737-2022
|View full text |Cite
|
Sign up to set email alerts
|

Risks of seasonal extreme rainfall events in Bangladesh under 1.5 and 2.0 °C warmer worlds – how anthropogenic aerosols change the story

Abstract: Abstract. Anthropogenic climate change is likely to increase the risk (probability of occurrence of a hazard) of extreme weather events in the future. Previous studies have robustly shown how and where climate change has already changed the risks of weather extremes. However, developing countries have been somewhat underrepresented in these studies, despite high vulnerability and limited capacities to adapt. How additional global warming would affect the future risks of extreme rainfall events in Bangladesh ne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Based on the HadRM3P model, Rimi et al (2019) attributed that a flash flood in northeastern Bangladesh driven by an extreme rainfall event in March 2017 was most likely due to anthropogenic forcing, instead of internal variability modes such as IOD or ENSO. Later, Rimi et al (2022) used a large ensemble regional climate model to investigate the influence of aerosols on the mean and extreme monsoon rainfall events, and found extreme rainfall events increase in the future due to global warming. The anthropogenic aerosols, however, suppress the increase of mean rainfall events during pre-monsoon and monsoon, whereas the increase of global mean surface temperature increases the rainfall (Rimi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the HadRM3P model, Rimi et al (2019) attributed that a flash flood in northeastern Bangladesh driven by an extreme rainfall event in March 2017 was most likely due to anthropogenic forcing, instead of internal variability modes such as IOD or ENSO. Later, Rimi et al (2022) used a large ensemble regional climate model to investigate the influence of aerosols on the mean and extreme monsoon rainfall events, and found extreme rainfall events increase in the future due to global warming. The anthropogenic aerosols, however, suppress the increase of mean rainfall events during pre-monsoon and monsoon, whereas the increase of global mean surface temperature increases the rainfall (Rimi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Later, Rimi et al (2022) used a large ensemble regional climate model to investigate the influence of aerosols on the mean and extreme monsoon rainfall events, and found extreme rainfall events increase in the future due to global warming. The anthropogenic aerosols, however, suppress the increase of mean rainfall events during pre-monsoon and monsoon, whereas the increase of global mean surface temperature increases the rainfall (Rimi et al, 2022). Tang et al (2022) analyzed the seasonal mean summer 2020 rainfall event over the northeast Indian subcontinent and found an anomalous anticyclone associated with the La Niña phase that contributed to the wettest summer rainfall event over this region since 1901.…”
Section: Introductionmentioning
confidence: 99%
“…However, the coastal areas have shown a higher rate of warming over the last five decades (Abdullah et al, 2022). A study investigated the trends of climate extremes in Bangladesh and concluded that mean monsoon seasonal rainfall can alter, posing significant challenges to agriculture, hydropower and the ecosystem (Rimi et al, 2022). Nepal has experienced extreme events due to climate extremes in recent decades.…”
Section: Introductionmentioning
confidence: 99%